Sex differences in the use of rhythm control strategies in patients with atrial fibrillation in FinACAF study. (3rd October 2022) - Kalatsova, K; Lehto, M; Inkovaara, J; Aro, A L; Halminen, O; Jaakkola, J; Penttila, T; Salmela, B; Airaksinen, K E J
Abstract: Aim: Women with atrial fibrillation (AF) have been reported to receive less antiarrhythmic therapies (AAT) than men. We assessed sex differences in AAT use in Finland. Methods: The FinACAF registry linked data from several nationwide registries covering all levels of care in addition to drug purchases and included records on all patients diagnosed with incident AF in Finland during 2007–2018. The outcomes of interest (use of antiarrhythmic drugs (AAD), cardioversions (CV), catheter ablation procedures and any AAT including all aforementioned rhythm control modalities) were identified based on procedure-specific codes and drug purchases. Sex differences in AAT use were analyzed in the entire cohort and separately in three age groups: <65 years, 65–74 years and ≥75 years using Fine-Gray subdistribution hazard regression with death as a competing risk and adjustments made for comorbidities, age and levels of income and education. Results: Altogether, 229565 patients (50.0% female; mean age 68.90±13.44 in men and 76.57±11.79 in women) with incident AF were identified. In the entire patient population, female sex was associated a higher incidence of AAD use and lower incidence of CVs and ablation procedures contributing to an overall slightly lower incidence of any AAT compared to men (Table 1). In the age group specific analyses, the lower incidence of CVs and higher incidence of AAD use in females were observed only in patients <65 years and <75 years, respectively, whereas the association of female sex with lower incidence of catheter ablation procedures was observed only in the age group ≥75 years. Conclusion: Our nationwide data showed no considerable sex difference in overall use of AAT in Finland. Despite a lower number of CVs in women, ablation procedures were performed almost equally and AADs were used more frequently in women compared to men. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Sydäntutkimussäätiö